RANCANG BANGUN SISTEM INFORMASI PERSEDIAAN OBAT DAN PERBEKALAN KESEHATAN PADA DINAS KESEHATAN KABUPATEN MUSI BANYUASIN - Ali Subhan Afrizal (Politeknik Sekayu, 2016)
Musi Banyuasin Department of Health already use computer to manage medicine supply and medical equipment, However it stil not efficient and uncoordinated very well, so when that data needed, it took a long time to do search and slowing down reporting process. Therefor author want to make a web-based information system using PHP programming language. With this information system can facilitate data collecting and able to ease every UPTD to do reporting and submission usage of drug supply and medical store. In adition, this system able to ease data searching process to make it faster and easier, also helping report processing to superior.